دور القدرات الإبداعية للعاملين في تحسين الأداء الوظيفي من خلال الكفاءات الذاتية )دراسة تطبيقية على العاملين بديوان عام وزارة التعليم العالي والبحث العلمي والابتكار سلطنة عمان ( - عبير بنت علي بن عوض
The personal competences of employees constitute one of the most important principles of management that attracted the attention of researchers in the field of corporate management as a firm foundation and vital element for organizational success. Without personal competences, employees would not be able to highlight their creative abilities, pose distinctive initiatives to solve the stubborn management problems, as well as to upgrade the institution’s job performance. This research aims to identify the role of employees’ creative competences in enhancing the job performance through personal competences at the Ministry of Higher Education, Research and Innovation in the Sultanate of Oman. The researcher has adopted the descriptive survey approach, which suits the nature of this study and its objectives. Due to the nature of the study, the researcher has adopted the quantitative technique using the cross-sectional method to collect the research data. As the researcher has developed a questionnaire consisting of (48) statements to collect the data relative to the three study variables, where the questionnaire was distributed to all the study population at the Ministry. The researcher has adopted the non-random sample to distribute the assessment tool (the questionnaire) to the respondents. As the researcher managed to obtain (300) questionnaires that are valid for statistical analysis, including (217) for males and (83) for females, which were entered into SPSS program, V. 26, to conduct the descriptive analyses. Furthermore, the SMART PLS program-V. 3 was used to conduct the Measurement Model to evaluate the validity and reliability of the data, and the Structural Model was used to study the structural relations between the research variables, where the validity of the research’s four hypotheses was proved. Considering the current research’s findings and conclusions, the researcher could formulate some proposals and recommendations that are relative to benefitting from the research results. This aims to enhance and develop the job performance of employees working at the Ministry on the one hand, and proposals for researchers who wish to conduct relevant scientific studies on the other hand. The research mainly aimed at identifying the extent of creative competences’ impact with its dimensions (identifying problems, fluency, authenticity, and flexibility) on enhancing the job performance (job tasks, roles, motives, and feedback) through personal competence (indirect experience, verbal persuasion, previous experiences, and emotional influence) on the employees at the Ministry.